Singing the second chimurenga (war of liberation): an Afrocentric elucidation of Simon Chimbetu’s selected songs - Maganga, Allan T.; Tembo, Charles; Dewah, Peterson (Unisa Press, 2016)
Oral sources such as proverbs, songs and folktales have been used to reconstruct people's identities. As a primary 'means of communication’, music is often used to capture or record people’s experiences in history. In Zimbabwe, Simon Chimbetu exemplifies one musician who is in search of his country’s past in as far as he uses his music to record the history of the liberation struggle. This article provides an in-depth examination of Chimbetu's selected songs. Singing after the war itself is over, it is argued, the music functions as a reference point to the citizens because it is a transcript of their past experiences, something which is essential to the present and future generations. By insisting on educating his audiences on the liberation struggle, Chimbetu satisfies Sankofan approach.